Culture organizations and style leadership to satisfaction work to improve their performance of teaching staff Bogor Agricultural University - Mayasari, Yiyis; Hubeis, Musa; ., Indupurnahayu (Jurnal Manajemen, 2018)
The aims of study were carried out the review of the influence in organizational culture and leadership style on job satisfaction to improve separately the performance of educational staff in the IPB and to determine which variables have the most dominant influence. Also, to study the influence of organizational culture, leadership style and job satisfaction in the performance of education personnel in IPB. The Primary data in this study were obtained from questionnaires distributed to respondents (staff) ini the Bureau, the Office and the Directorate of IPB. Data acquisition was applied to the 168 speakers, using tools like questionnaire and finally, analyzed statistically elaborated by Path Analysis (two substructures contained in the Statistical Package for Social Science (SPSS) version 21). Result of the analysis showed a direct influence of organizational culture on employee performance. Leadership style has no effect on employee performance: job statisfaction effects the performance of employees. Organizational culture has influence on job satisfaction and leadership style influence on job satisfaction and positive influence.